2022
DOI: 10.1002/eap.2645
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of cold snaps, rain, and agriculture on the fledging success of a declining aerial insectivore

Abstract: Climate change predicts the increased frequency, duration, and intensity of inclement weather periods such as unseasonably low temperatures (i.e., cold snaps) and prolonged precipitation. Many migratory species have advanced the phenology of important life history stages and, as a result, are likely to be exposed to these periods of inclement spring weather more often, therefore risking reduced fitness and population growth. For declining avian species, including aerial insectivores, anthropogenic landscape ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…It is thus imperative that future work focuses not only on how agricultural practices or global climate change independently impact declining avian species, but also on how these factors may interact with one another. This importance is due to the ability of growing broods or breeding parents to manage extreme weather is potentially lower within more agro-intensive landscapes (Eng et al, 2019;Evans et al, 2003;Garrett et al, 2022c;Grue et al, 1997;Tapper et al, 2020). Finally, our results provide evidence that aerial insectivore declines may be related to agricultural intensification through a trophic pathway.…”
Section: Durationmentioning
confidence: 69%
“…It is thus imperative that future work focuses not only on how agricultural practices or global climate change independently impact declining avian species, but also on how these factors may interact with one another. This importance is due to the ability of growing broods or breeding parents to manage extreme weather is potentially lower within more agro-intensive landscapes (Eng et al, 2019;Evans et al, 2003;Garrett et al, 2022c;Grue et al, 1997;Tapper et al, 2020). Finally, our results provide evidence that aerial insectivore declines may be related to agricultural intensification through a trophic pathway.…”
Section: Durationmentioning
confidence: 69%
“…The one exception was the interaction between precipitation and cropland, where wetter conditions were associated with negative biodiversity outcomes and drier conditions were associated with positive biodiversity outcomes for both species richness and abundance regardless of changes in cropland. That neither species richness nor abundance responded to changes in cropland cover when there were simultaneous changes in precipitation is surprising since other research has shown that agriculture can exacerbate the negative effects of increased precipitation on fledging success (Garrett et al ., 2022) and impact differences in occupancy between wet and dry areas (Frishkoff et al ., 2016).…”
Section: Discussionmentioning
confidence: 92%
“…Not surprisingly, cold stress has been widely demonstrated to increase avian mortality and susceptibility to enteric infection ( Mallmann, 1934 ; Thaxton et al, 1974 ; Soerjadi et al, 1979 ; Matsumoto and Huang, 2000 ; Borsoi et al, 2015 ). Indeed, the frequent and intense weather events ushered in by climate change, including rapid ambient temperature swings such as cold snaps, are of particular concern for avian species ( Garrett et al, 2022 ). Whether the stress-induced modulation of enteric neurochemical concentrations constitutes, in part, the mechanism driving avian susceptibility to infection following cold stress is unknown.…”
Section: Introductionmentioning
confidence: 99%